A structural approach for analyzing fiscal equalization - Audun Langørgen (Statistics Norway, Research Department, 2012)
Many countries apply cost-equalization and/or fiscal capacity equalization formulas to enable sub-national governments to provide comparable service standards at comparable tax rates. This paper demonstrates how measures of expenditure needs and fiscal capacity can be derived from a structural model of local government spending and taxing behavior. The structural parameters are shown to provide the information required to implement equalization according to the principle of horizontal equity.
Keywords: H71; H72; 330; Fiscal Equalization; Expenditure Needs; Fiscal Capacity; Structural Modeling